FOOD DISTRIBUTION BEFORE AND DURING THE COVID-19 PANDEMIC AT THE NUTRITION INSTALLATION OF THE TUGUREJO REGIONAL GENERAL HOSPITAL SEMARANG: A DESCRIPTIVE STUDY - William Ben Gunawan; Taqiyla Aziza Kesiananda; Syafirah Kholifatul Jannah; Cholip Sutiyati; Diana Nur Afifah; Choirun Nissa (Jurnal Online Keperawatan Indonesia, 2022)
The COVID-19 pandemic has made some of the activities carried out differently than before the pandemic. The handling and treatment of COVID-19 are inseparable from the contribution of healthcare facilities and hospitals. The physical distancing recommendation to prevent the transmission of the COVID-19 virus that supports patient care has made the food service management in hospitals – especially food distribution – undergo several modifications. The purpose of this study was to analyze the differences in the food distribution process at the Nutrition Installation of Tugurejo Regional General Hospital Semarang before and during the COVID-19 pandemic. This descriptive study used observational methods and online interviews using structured questions. Data related to the food distribution process before and during the pandemic was acquired through interviews with the Head of Research and Development of the Nutrition Installation of Tugurejo Regional General Hospital Semarang, while observation was only done during the pandemic. There were differences in the food distribution system before and after the pandemic at the Nutrition Installation of Tugurejo Regional General Hospital Semarang related to the Bed Occupancy Rate (BOR), nutritional service classes, distribution processes, food distribution time, places to eat (food serving media), hygiene and sanitation, as well as measuring food acceptance. The food service management focused on providing the best services of patient care before the pandemic; and highlighted the importance of physical distancing, sanitation, and hygiene during the pandemic. Understanding the changes needed in food distribution services at the hospital during the COVID-19 pandemic will give insights into the approach to improve patient care and prevent the transmission of the COVID-19 virus.